Identification of Three Exercise-induced Mortality Risk Factors in Patients with COPD. (1st December 2014) - Yoshimura, Kenji; Maekura, Ryoji; Hiraga, Toru; Miki, Keisuke; Kitada, Seigo; Miki, Mari; Tateishi, Yoshitaka; Mori, Masahide
Abstract The survival rate of chronic obstructive pulmonary disease (COPD) patients with severely reduced exercise capacity is extremely low. We recently identified three life-threatening pathophysiological conditions during cardiopulmonary exercise testing (CPET): (1) exercise-induced hypoxemia, (2) sympathetic overactivity, and (3) progressive respiratory acidosis at low-intensity exercise. The present prospective observation study aimed to determine whether these parameters constitute risk factors of mortality in moderate-to-very severe COPD. Ninety-six COPD patients were followed-up, monthly, for >3 years. Subsequently, spirometry and CPET were performed to examine parameters of exercise-induced hypoxemia ([PaO2 slope, mmHg/L · min−1] = Decrease in PaO2/ΔV˙ O2 (Difference in ΔV˙ O2 between at rest and at peak exercise)), progression of acidosis ([ΔpH/ΔV˙ O2, /L · min−1] = Decrease in pH/ΔV˙ O2), and sympathetic overactivity ([Δnorepinephrine (NE)/ΔV˙ O2, ng/mL/L · min−1] = Increase in NE/ΔV˙ O2). Univariate analysis revealed a significant association between the three conditions with increased mortality. Kaplan–Meier analysis showed that the quartile combining the steepest PaO2 slope (≤–55 mmHg/ΔV˙ O2 [L/min]), steepest decrease in arterial blood pH (≤ –1.72/ΔV˙ O2 [L/min]), and most rapid increase in plasma NE level (≥ 5.2 ng/VO2 [L/min]) during incremental exercise was associated with higher all-cause mortality. These conditions showed cumulative effects on COPD patients' survival. Multivariate analyses revealed that these three life-threatening factors are also independent predictors of mortality based on age, heart rate and PaO2 at rest, body mass index, and forced expiratory volume in 1 s. Thus, these new exercise-induced mortality risk factors may lead to more efficient pulmonary rehabilitation programs for COPD patients based on patient-specific exercise-induced pathophysiological profiles.